Hubungan Antara Biaya Tidak Resmi Dan Loyalitas Pengunjung Di Kawasan Wisata Alun-Alun Kidul - Kalore, Agustina Toya; Dhawe, Eprilia Ribianti; Chelsiana, Hilaria; Hermawan, Hary; Ardanari, Fransisca Ratna (Journal of Tourism Sciences, Technology and Industry, 2025)
The increasing number of tourist visits to Alun-Alun Kidul Yogyakarta brings with it various problems, one of which is the existence of unofficial fees that have the potential to reduce the level of visitor satisfaction and loyalty. Unofficial fees such as illegal parking fees, additional fees for attractions that are not in accordance with the provisions, and fees from unauthorized parties are considered detrimental to tourists and can influence their decision to return. This study uses a quantitative method with a descriptive design. Data were collected through a questionnaire survey involving 50 tourists who had visited Alun-Alun Kidul in the last six months and had experience or knowledge of these unofficial fees. Data analysis was carried out using descriptive statistics, Pearson correlation tests, and reliability tests to measure the relationship between unofficial fees and tourist loyalty. The results of the study show that unofficial fees have a negative impact on tourist loyalty. The higher the unofficial fees felt by visitors, the lower their intention to return or recommend this tourist area. Several indicators show a strong and significant correlation. The conclusion of this study emphasizes the importance of supervision and transparency in cost management in tourist areas. It is expected that local managers and governments can tighten supervision of illegal levies and set clear cost standards, in order to create a safe and comfortable tourism environment and increase tourist loyalty.